Utilization of Mentzer Index to Discriminate Between Beta Thalassemia Minor and Anemia of Iron Deficiency, Followed by HPLC - Muhammad Idrees, Jibran Umar Ayub Khan, Huma Riaz, Munawar Ali Shah, Hamidullah Shah, Syed Mohammad Haris, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Aim was to evaluate the sensitivity and specificity of Mentzer index in differentiating beta thalassemia minor from anemia of Iron deficiency. Materials and Methods: A cross-sectional study conducted in Hematology unit of Hayatabad Medical Complex .Sampling was done non-consecutively. A total of 860 cases with value of Hemoglobin less than 11 Gm/DL were counted. In all the selected cases full blood count were checked and Mentzer Index mean corpuscular volume [MCV] per RBCs count )was calculated. Value of <13 suggests the diagnosis of β Thalassemia minor/trait while more than 13 value is more indicative of Iron deficiency anemia (IDA). Confirmation of diagnoses was made by hemoglobin study using HPLC. Values for specificity and sensitivity for Mentzer Index were calculated for the two differentials of microcytic hypochromic anemia presenting with microcytosis and hypochromia. Results: Mean hemoglobin level of patients was 9.01±1.85. Minimum and maximum hemoglobin value was 2.90 and 11 g/dl. Mean RCB count was 4.66±4.59 minimum and maximum RCB count was 1.07 and 136. Mean MCV value was 63.89±9.01. Minimum and maximum MCV value was 39.40 and 92.10 respectively. Men Mentzer index was 15.70±7.68. Minimum and maximum Mentzer index value was 7.80 and 10.7 respectively. Based on Mentzer index criteria 489(56.86%) patients had iron deficiency anemia and 371(43.14%) patients had higher suspicion of beta thalassemia. Conclusion: It was concluded that for differentiation among Beta thalassemia minor and anemia of iron deficiency , Mentzer Index can be beneficial to discriminate with a high sensitivity as well as specificity percentage and thus through a cost effective way, only suspected cases of beta thalassemia trait/minor can be further confirmed by Hb Electrophoreses. Keywords: Mentzer Index, iron deficiency Anemia, beta Thalassemia minor